Comparison of intratumoral heterogeneity of HER2 expression between primary tumor and multiple organ metastases in gastric cancer: Clinicopathological study of three autopsy cases and one resected case. (31st March 2015) - Saito, Takuya; Kondo, Chihiro; Shitara, Kohei; Ito, Yuichi; Saito, Noriko; Ikehara, Yuzuru; Yatabe, Yasushi; Yamamichi, Keigo; Tanaka, Hideo; Nakanishi, Hayao
<x xml:space="preserve">Abstract</x> Intratumoral heterogeneity of HER2 expression in the metastatic foci of HER2‐positive advanced gastric cancer remains unclear. In this study, we compared HER2 expression between primary and metastatic tumors in HER2–positive three autopsied cases and one resected case with multiple organ metastases by immunohistochemistry (IHC) and dual color in situ hybridization (DISH). All four cases judged positive (IHC3+) at the primary tumor tissues showed varying HER2 gene amplification (GA) status. One homogeneously HER2‐positive autopsied case (Case 1) and one intratumorally heterogeneous positive resected case (Case 2) with high GA showed a homogeneous positive staining pattern in all the metastatic foci. One heterogeneously HER2‐positive autopsied case (Case 3) with low GA showed a partially heterogeneous HER2 staining pattern in all the metastatic foci. In contrast, one heterogeneously HER2‐positive autopsied case (Case 4) with equivocal GA showed a completely heterogeneous HER2 staining pattern in the metastatic foci. These results indicate that HER2‐positive gastric cancers with low to high GA at the primary tumor show substantially homogeneous HER2 overexpression in the metastatic foci, whereas HER2‐positive gastric cancers with equivocal GA expressed HER2 heterogeneously within the metastatic tumor, suggesting that metastatic foci of the latter HER2‐positive cases would be potentially resistant to trastuzumab.